Molecular dan Genomic Biomarker sebagai Deteksi Dini pada Diagnosis Kanker Prostat - Jihan Audini Karim (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Prostate cancer is a noncutaneous malignancy in men, a heterogeneous disease with varying clinical outcomes. The modern clinical approach to prostate cancer emphasizes the need for treatment to avoid overdiagnosis and overtreatment. Advances in understanding of the pathogenesis of prostate cancer, coupled with technological innovations, have facilitated the development and validation of a number of molecular biomarkers, representing a variety of tested macromolecules from a wide variety of patient samples, to aid clinical management of prostate cancer, including early detection, diagnosis, prognostication, and selection. targeted therapy. Prostate cancer is asymptomatic in the early stages of the disease, there are various clinical-pathological signs and disease progression, and is characterized mostly by indolent cancer types. Therefore, it is imperative to develop individualized approaches for early detection, disease stratification (indolent vs. aggressive) and prediction of treatment response for prostate cancer. This article is a review article in which researchers review the current state of use of genomic biomarkers for early detection of prostate cancer, demonstrating the function of molecular biomarkers in clinical practice. The result of this review article is that the available genomic and proteomic tests can increase the predictive value of the PCa risk classification system based on clinical variables.